The Impact of environmental policy stringency on Korean exports of environmental goods - LEE, Minkyung (KDI School, 2018)
This paper studies the effects of two aspects of stringent environmental policy on Korea’s exports of environmental goods: 1. The effects of a trade partner’s environmental policy stringency; and 2. The effects of Korea’s environmental policy stringency. This paper uses panel data from 2002 to 2012 for OECD and BRIICS countries. The gravity model is implemented, with EPS index (OECD) serving as an indicator for environmental policy stringency. Based on the effects being analyzed by this paper, the empirical results show: 1. The stringent environmental policy of a trade partner has a positive effect on Korea’s exports because the market is greater in countries with stricter environmental policy; 2. Korea’s environmental policy has a decisive influence on the increase in Korea’s exports of environmental goods, which is consistent with the Porter Hypothesis. Stringent environmental policies should therefore be utilized to strengthen the competitiveness of Korea's environmental goods and a certain level must be maintained to promote the export of environmental goods.
Thesis(Master) --KDI School:Master of Development Policy,2018